Counterfactual Reasoning in Non-psychotic First-Degree Relatives of People with Schizophrenia - Albacete, Auria; Contreras, Fernando; Bosque, Clara; Gilabert, Ester; Albiach, Ángela; Menchón, José M.; Crespo-Facorro, Benedicto; Ayesa-Arriola, Rosa (Frontiers in Psychology, 2016)
Counterfactual thinking (CFT) is a type of conditional reasoning that enables the generation of mental simulations of alternatives to past factual events. Previous research has found this cognitive feature to be disrupted in schizophrenia. At the same time, the study of cognitive deficits in unaffected relatives of people with schizophrenia has significantly increased, supporting its potential endophenotypic role in this disorder. Using an exploratory approach, the current study examined CFT for the first time in a sample of non-psychotic first-degree relatives of schizophrenia patients (N=43), in comparison with schizophrenia patients (N=54) and healthy controls (N=44). A series of tests that assessed the “causal order effect” in CFT and the ability to generate counterfactual thoughts and counterfactually derive inferences using the Counterfactual Inference Test was completed. Associations with variables of basic and social cognition, levels of schizotypy and psychotic-like experiences in addition to clinical and sociodemographic characteristics were also explored. Findings showed that first-degree relatives generated a lower number of counterfactual thoughts than controls, and were more adept at counterfactually deriving inferences, specifically in the scenarios related to regret and to judgements of avoidance in an unusual situation. No other significant results were found. These preliminary findings suggest that non-psychotic first-degree relatives of schizophrenia patients show a subtle disruption of global counterfactual thinking compared with what is normally expected in the general population. Because of the potential impact of such deficits, new treatments targeting CFT improvement might be considered in future management strategies.